2019
DOI: 10.29244/jfs.3.1.15-29
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Family Function and Adolescent Autonomy in the Rural and Urban Area

Abstract: <p>This study aims to analyze the function of families in urban and rural areas as well as its relationship with adolescent autonomy by using cross sectional study method. The data collection time was conducted in September 2016. By proportional random sampling method, there were 72<br />samples at SMPN 2 Bogor (representing urban area) and 72 people at SMPN 2 Parung (representing rural area). Research data includes family characteristics, family functions divided into 3 dimensions (10 sub-scales) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The study cited was conducted with adolescents from a medium‐sized city (population of approximately 400 000 residents), whereas the present investigation was conducted in a smaller city with a larger rural population. Another study found that family functioning was better in areas with rural characteristics and that adolescents in rural areas had closer family ties and were more dependent on the family 29 . Therefore, it is likely that the OHL of parents/guardians is more of a determinant of the use of dental services by adolescents in contexts similar to that of the present investigation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The study cited was conducted with adolescents from a medium‐sized city (population of approximately 400 000 residents), whereas the present investigation was conducted in a smaller city with a larger rural population. Another study found that family functioning was better in areas with rural characteristics and that adolescents in rural areas had closer family ties and were more dependent on the family 29 . Therefore, it is likely that the OHL of parents/guardians is more of a determinant of the use of dental services by adolescents in contexts similar to that of the present investigation.…”
Section: Discussionsupporting
confidence: 51%
“…Another study found that family functioning was better in areas with rural characteristics and that adolescents in rural areas had closer family ties and were more dependent on the family. 29 Therefore, it is likely that the OHL of parents/guardians is more of a determinant of the use of dental services by adolescents in contexts similar to that of the present investigation.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, higher socioeconomic status and living in an urban area may expose adolescents to less quality time with their parents which may make them more susceptible to mental health problems. Reversely, those with lower socio-economic status or living in rural areas may experience more social cohesion both within households as well as in the community [51]. Maintaining support, contact, everyday activities at home, and forming supportive peer relationships may lower the risk of CMD in adolescents [52].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Previous study show that family function correlation with family resilence, so that the application of the eight functions is to realize family welfare, namely being able to live a good life where a person feels satisfied both with activities carried out routinely in meeting the basic needs of life and relationships with other people and with their environment (Lado et.al, 2022;Ningsih & Herawati, 2017). Mulyati and Martiastuti (2018) mentioned that family functioning of rural families is better than in urban areas, although it did not show statistically significant differences. Families receiving BPJS contribution assistance will affect the implementation of eight family functions, because for some families from low socioeconomic groups contribution assistance provided by the government will secure part of the allocation of family resources for basic needs such as food and drink which are basically not good (Layliyah, 2013).…”
Section: Introductionmentioning
confidence: 99%